Guidance for evidence-informed policies about health systems: rationale for and challenges of guidance development. - Xavier Bosch-Capblanch (Public Library of Science (PLoS), 2012)
In the first paper in a three-part series on health systems guidance, Xavier Bosch-Capblanch and colleagues examine how guidance is currently formulated in low- and middle-income countries, and the challenges to developing such guidance.